Automatic registration of dairy cows grazing behaviour on pasture - Blomberg, Kristina (2011)
Information regarding cows grazing behaviour and time spent grazing can be of great interest to dairy farmers, since this information can indicate how well suited the pasture is to the cows. Feed intake at pasture is however challenging to measure. Automated systems for monitoring the behaviour of cows within dairy production have become increasingly important and relatively common.